ANALISIS FAKTOR PRODUKSI PADI SAWAH DI DESA TOMPASOBARU DUA KECAMATAN TOMPASOBARU - Klivensi I. Mafor; Esry O.H. Laoh; Joachim N.K. Dumais; Tommy F. Lolowang (COCOS, 2015)
ABSTRACTThe objective of this research is to identify this study is what factors influence the use of paddy rice production in the Tompasobaru Dua Village District. The data collected in this research was primary data. Primary data obtained from interviews with farmers using a questionnaire. The sampling method is simple random sampling, the number of farmers as much as 60 samples .The analysis used in this research is to use multiple linear regression analysis. The dependent variable is the production of rice and the independent variable is the land area , the use of urea, fertilizer use ponska, and labor. The research result showed that the factors of production that significantly affect rice production Tompasobaru Dua Village, Tompasobaru Sub District were land area, fertilizer use of ponska, and labor